Examination of community and consumer nutrition, tobacco and physical activity environments at food and tobacco retail stores in three diverse North Carolina communities - D'Angelo, Heather (Prev Med Rep, 2015)
To advance our understanding of multiple health-related dimensions of the built environment, this study examined associations among nutrition, tobacco, and physical activity community and consumer environments. Community environment measures included supermarket access, tobacco outlet density, and physical activity resource density in store neighborhoods. Cross-sectional observations of the nutrition, tobacco and physical activity environments were conducted in 2011 at and around 303 food stores that sold tobacco products in three North Carolina counties. Pearson correlation coefficients and multiple linear regression were used to examine associations between community and consumer environments. Correlations between community nutrition, tobacco, and physical activity environments ranged from slight to fair (− 0.35 to 0.20) and from poor to fair (− 0.01 to − 0.38) between consumer environments. Significant relationships between consumer tobacco and nutrition environments were found after controlling for store and neighborhood characteristics. For example, stores with higher amounts of interior tobacco marketing had higher healthy food availability (p = 0.001), while stores with higher amounts of exterior tobacco marketing had lower healthy food availability (p = 0.02). Community and consumer environments for nutrition, tobacco, and physical activity were interrelated. Measures that assess single aspects of community or consumer environments could miss characteristics that may influence customer purchasing. Even chain supermarkets, typically regarded as healthful food sources compared to smaller food stores, may expose customers to tobacco marketing inside. Future research could explore combining efforts to reduce obesity and tobacco use by addressing tobacco marketing, healthy food availability and physical activity opportunities at retail food outlets.